1994
DOI: 10.1080/07349349408905235
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Drying Heat and Moisture Content on the Maximum Temperature Rise During Spontaneous Heating of a Moist Coal Pile

Abstract: Recent work has suggested that the moisture of a sub-bituminous coal may exist in three forms, namely free moisture, loosely bound moisture and tightly bound moisture (these moistures do not include chemically bound moisture). The complete drying of each type of moisture requires a stepwise changing amount of energy, known as the heat of drying. This stepwise change in the heat of drying in relation to the moisture content of coal was, in the current study, incorporated into a mathematical model that describes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Many factors, including non-fulfillment of the basic principles of fire prevention, the use of improper technologies, as well as the absence of waste segregation and compaction in the storage process, resulted in self-ignition of mine waste dumps. Coal and pyrite included in waste material are oxidized when exposed to air and water vapor, which leads to self-heating of the deposited material, and in consequence to fires [2,3]. Coal mine waste dumps are therefore often thermally active objects characterized by high internal and surface temperatures and presence of exhalation zones emitting exhaust gases [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many factors, including non-fulfillment of the basic principles of fire prevention, the use of improper technologies, as well as the absence of waste segregation and compaction in the storage process, resulted in self-ignition of mine waste dumps. Coal and pyrite included in waste material are oxidized when exposed to air and water vapor, which leads to self-heating of the deposited material, and in consequence to fires [2,3]. Coal mine waste dumps are therefore often thermally active objects characterized by high internal and surface temperatures and presence of exhalation zones emitting exhaust gases [4].…”
Section: Introductionmentioning
confidence: 99%
“…free moisture (chemically bound moisture is not included) which may influence the susceptibility of a coal to spontaneously combust (Chen, 1994). Some researchers have concluded that a low moisture content may assist rather than retard the combustion whilst a high moisture retards the combustion(B.…”
Section: (A) Moisture Contentmentioning
confidence: 99%